Optimizing Coastal and Small Island Areas through Industrial Reclamation: An Examination through the Lens of Utilitarianism Theory - Faradillah, Candra Vira (Universitas Islam Negeri Walisongo Semarang, 2023)
Indonesia, as the largest archipelagic country in the world with more than 17,000 islands, has the potential to become the world's maritime axis through optimizing marine resources. One of the policies taken was converting coastal areas and small islands as industrial reclamation areas. However, they faced several real problems and impacts. This research normatively analyzes the disharmony of reclamation regulations and the impact of policies on changing the function of coastal areas and small islands as industrial reclamation areas, focusing on the perspective of John Stuart Mill's utilitarianism theory. The research results show the absence of national law, which causes overlapping authority of agencies, a lack of harmony in perceptions between agencies, and a lack of specific regulations for reclamation requirements—judging from J.S.'s theory of utilitarianism. Mill, the current reclamation policy has not equally provided benefits and happiness because the negative impact is more significant than the expected positive. This research highlights the need for substantial improvements in the legal framework and implementation of reclamation policies to minimize negative impacts and increase positive contributions for stakeholders.Indonesia, sebagai negara Archipelagic terbesar di dunia dengan lebih dari 17.000 pulau, memiliki potensi untuk menjadi poros maritim dunia melalui optimalisasi sumber daya kelautan. Salah satu kebijakan yang diambil adalah alih fungsi wilayah pesisir dan pulau-pulau kecil sebagai kawasan reklamasi industri, namun, menghadapi sejumlah permasalahan dan dampak nyata. Penelitian ini secara normatif menganalisis disharmonisasi pengaturan reklamasi dan dampak kebijakan alih fungsi wilayah pesisir dan pulau-pulau kecil sebagai kawasan reklamasi industri, dengan fokus pada perspektif teori utilitarianisme John Stuart Mill. Hasil penelitian menunjukkan ketidakadaan hukum nasional yang menyebabkan tumpang tindih kewenangan instansi, kurangnya keselarasan persepsi antar instansi, dan kekurangan aturan khusus untuk persyaratan reklamasi. Ditinjau dari teori utilitarianisme J.S. Mill, kebijakan reklamasi saat ini belum memberikan kemanfaatan dan kebahagiaan secara merata, karena dampak negatifnya lebih besar dibandingkan dampak positif yang diharapkan. Penelitian ini menyoroti perlunya perbaikan substansial dalam kerangka hukum dan implementasi kebijakan reklamasi untuk meminimalkan dampak negatif dan meningkatkan kontribusi positif bagi pemangku kepentingan.